Export-Oriented Economy-A New Model of Development for the Republic of Moldova - Corina COLIBAVERDI; Boris CHISTRUGA (CSIE Working Papers Series, 2016)
The severe impact of the global financial crisis on Moldovan economy was accompanied by an increase in unemployment and fluctuations of inflation, reduction of foreign direct investment and external trade. One of the most important lessons of the global financial crisis of 2009 for the Republic of Moldova was accentuating the necessity to give up to the support of remittances, which determines that our economy is based on consumption and imports and should follow a qualitative model of growth. Consumption based growth, due to remittances is not qualitative growth and does not create jobs. That’s why it is a vital necessity for Moldova to pass to a new path of economic growth, namely to an economic growth based on increase competitiveness.